Restoration of a bridge structure on the example of a brick railway viaduct in Zielona Góra - Juszczyk, Artur (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the successful restoration of a railway viaduct in Zielona Góra. The carried out reconstruction, in the scope of increasing the clearance gauge under the bridge, made it possible to increase operational safety while maintaining the existing structure of the object. The described case serves as an example of actions facilitating the further historic use of transportation infrastructure structures while limiting financial outlays for adapting them to current expectations.
Keywords: historic bridge; reconstruction; railway viaduct; most historyczny; rekonstrukcja; wiadukt kolejowy